Applicability of shear wave elastography of the major salivary glands: values in healthy patients and effects of gender, smoking and pre-compression - Mantsopoulos, Konstantinos; Klintworth, Nils; Iro, Heinrich; Bozzatoy, Alessandro (Ultrasound in Medicine and Biology, 2015)
Our aim in this study was to determine normal shear wave elastography (SWE) values for the parenchyma of the major salivary glands and to evaluate the influences of gender, smoking, side and type of gland and varying amounts of ultrasound probe pressure on SWE values. Twenty-five consecutive healthy patients were examined with ultrasound. SWE velocities were measured with acoustic radiation force imaging in the hilum and central region of both glands with "normal" and very low pressure. Mean SWE velocities were 1.854 m/s for the parotid gland and 1.932 m/s for the submandibular gland. No statistically significant differences were detected between males and females, smokers and non-smokers, parotid and submandibular gland and left and right sides. Greater pre-compression with the ultrasound probe resulted in a statistically significant increase in the SWE values of both salivary glands (p < 0.000). The degree of pre-compression by the ultrasound transducer should be standardized, so that the reliability and reproducibility of this innovative method can be improved.
EVALuna2:19987